An Economic survey of citrus farming in the union of South Africa during the period 1948-1950 with special reference to the organisation and management of 67 farms in the Eastern Cape Coastal Area - Bestbier, N.A.B. (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria,1952.